Financial management and policy - Van Horne, James C. (Englewood Cliffs, N.J. Prentice-Hall, 1968)
Contents: Introduction; investment in assets; financing in theory and dividend policy; long-term financing; management of current assets; short and intermediate-term financing; expansion and contraction; the tools of financial analysis and control.
Includes bibliographies
Keywords: Quản trị kinh doanh